Analysis of the C9orf72 Gene in Patients with Amyotrophic Lateral Sclerosis in Spain and Different Populations Worldwide - García-Redondo, Alberto; Dols-Icardo, Oriol; Rojas-García, Ricard; Esteban-Pérez, Jesús; Cordero-Vázquez, Pilar; Muñoz-Blanco, José Luis; Catalina, Irene; González-Muñoz, Miguel; Varona, Luis; Sarasola, Esther; Povedano, Monica; Sevilla, Teresa; et al. (Human mutation, 2013)
ABSTRACT A hexanucleotide repeat expansion in chromosome 9 open reading frame 72 (C9orf72) can cause amyotrophic lateral sclerosis (ALS) and/or frontotemporal dementia (FTD). We assessed its frequency in 781 sporadic ALS (sALS) and 155 familial ALS (fALS) cases, and in 248 Spanish controls. We tested the presence of the reported founder haplotype among mutation carriers and in 171 Ceph Europeans from Utah (CEU), 170 Yoruba Africans, 81 Han Chinese, and 85 Japanese subjects. The C9orf72 expansion was present in 27.1% of fALS and 3.2% of sALS. Mutation carriers showed lower age at onset (P = 0.04), shorter survival (P = 0.02), greater co‐occurrence of FTD (P = 8.2 × 10−5), and more family history of ALS (P = 1.4 × 10−20), than noncarriers. No association between alleles within the normal range and the risk of ALS was found (P = 0.12). All 61 of the mutation carriers were tested and a patient carrying 28 hexanucleotide repeats presented with the founder haplotype. This haplotype was found in 5.6% Yoruba Africans, 8.9% CEU, 3.9% Japanese, and 1.6% Han Chinese chromosomes.